Religious Minorities during Russia’s Transition from Atheism to Secularism - Agadjanian, Alexander (Research in the social scientific study of religion, 2000)
This paper describes the religious "market" in post-U.S.S.R. Russia, with the most attention to religious minorities. In Russia, as well as in some other post-communist countries, the new situation does not fit in any existing typology of religious life. On the one hand, there is a "rehabilitation" of religion after decades of an antireligious sociopolitical environment. On the other hand, there is the process of accommodating to a new global postreligious modernity that presumes religious pluralism within a secularized setting. The paper especially considers the situation of minority religions in a country dominated by one powerful denomination, Russian Orthodoxy. This study is based on a series of interviews conducted in 1995 and 1996 among leaders and ordinary members of several minority communities including Pentecostals, Lutherans, Rosa (Dew) Church1, and New Apostolic Church, all in Moscow.